Abducing Denite Descriptions Links - Freitas, Sérgio A. A.; Lopes, José Gabriel P.; Menezes, Crediné S. (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL); 2004: Anais do II Workshop em Tecnologia da Informação e da Linguagem Humana, 2004)
In this article we propose a methodology to solve functional definite noun anaphora. Our approach uses an abductive scheme both to propose an antecedent and to find a possible relation between the anaphoric entity and its antecedent. The determination of the antecedent and the anaphoric relation uses among other informations: the gender, the number, the entity ontology and the focus in order to establish a set of pragmatic rules. Those pragmatic rules are used by the abductive scheme to solve the functional anaphora.